2018
DOI: 10.1177/0269215518779122
|View full text |Cite
|
Sign up to set email alerts
|

Short- and long-term effects of pulmonary rehabilitation for idiopathic pulmonary fibrosis: a systematic review and meta-analysis

Abstract: In patients with IPF, pulmonary rehabilitation showed short-term effects in enhancing exercise capacity and health-related quality of life, while it had no detectable effects at long-term follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 36 publications
4
43
2
Order By: Relevance
“…However, no clear conclusions can be drawn in severe ILD and data on long-term effects of pulmonary rehabilitation in this advanced cohort are still sparse [156]. Current evidence on pulmonary rehabilitation in IPF shows significant short-term effects on improving exercise capacity (6MWD) and HRQL, while long-term effects are not maintained [157]. In addition, pulmonary rehabilitation has been shown to be useful in patients referred to lung transplantation [158].…”
Section: Pulmonary Rehabilitationmentioning
confidence: 99%
“…However, no clear conclusions can be drawn in severe ILD and data on long-term effects of pulmonary rehabilitation in this advanced cohort are still sparse [156]. Current evidence on pulmonary rehabilitation in IPF shows significant short-term effects on improving exercise capacity (6MWD) and HRQL, while long-term effects are not maintained [157]. In addition, pulmonary rehabilitation has been shown to be useful in patients referred to lung transplantation [158].…”
Section: Pulmonary Rehabilitationmentioning
confidence: 99%
“…Depression and anxiety have been described in around 25% of patients with IPF [55][56][57] . Depression and chronic physical illness are in reciprocal relationship with one another: not only do many chronic diseases cause higher rates of depression, but depression has been shown to decrease the potential benefits of the treatment approach 58 . Depression and anxiety may also impact on medication adherence 55,56 (Fig.…”
Section: Mental Wellbeing and Physical Healthmentioning
confidence: 99%
“…Another issue is one associated with individualisation and standardisation of the rehabilitation programme, taking into account the patient's capabilities and preferences and resulting, among others, from the degree of functional impairment, need for oxygen therapy and comorbidities. Another controversial question is that of the duration of the effects of rehabilitation, since many authors claim that the effects last up to 6 [307,313,321], 11 [326] or even 12 months [325] after completing the programme, while others do not confirm its lasting beneficial effects in a longer term [315,321]. Lack of unequivocal data confirming distant effect indicates it is necessary to use rehabilitation in a continuous and systematic way.…”
Section: Commentarymentioning
confidence: 99%
“…The most recent meta-analyses of 5 randomised trials involving more than 130 IPF patients divided into a group of subjects receiving rehabilitation and a control group demonstrated an improvement in exercise tolerance, reduction of symptoms and quality of life improvement [320]. Another meta-analysis of 4 randomised trials (a total of 142 subjects) confirmed beneficial short-term effects of rehabilitation on exercise capacity and quality of life but failed to confirm any distant effects [321]. The most recent meta-analysis of 7 studies involving 190 IPF patients demonstrated improved exercise capacity measured as distance in the 6MWT and improved quality of life [322].…”
Section: Introductionmentioning
confidence: 99%